2017
DOI: 10.1016/j.addr.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Decision support systems for personalized and participative radiation oncology

Abstract: A paradigm shift from current population based medicine to personalized and participative medicine is underway. This transition is being supported by the development of clinical decision support systems based on prediction models of treatment outcome. In radiation oncology, these models 'learn' using advanced and innovative information technologies (ideally in a distributed fashion - please watch the animation: http://youtu.be/ZDJFOxpwqEA) from all available/appropriate medical data (clinical, treatment, imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 310 publications
2
103
0
1
Order By: Relevance
“…An example; (1) in [19] was developing the DSS only in tertiary care use, (2) in [20] was developing the DSS also only in tertiary care use, (3) in [21] was developing the DSS only in secondary care use and many more as such as shown in Table 2. These means current decision making in healthcare is diagnosed based on a particular stage (primary care, secondary care, tertiary care or etc.).…”
Section: N Mahiddin Et Al J Fundamappl Sci 2017 9(5s) 144-167 150mentioning
confidence: 99%
“…An example; (1) in [19] was developing the DSS only in tertiary care use, (2) in [20] was developing the DSS also only in tertiary care use, (3) in [21] was developing the DSS only in secondary care use and many more as such as shown in Table 2. These means current decision making in healthcare is diagnosed based on a particular stage (primary care, secondary care, tertiary care or etc.).…”
Section: N Mahiddin Et Al J Fundamappl Sci 2017 9(5s) 144-167 150mentioning
confidence: 99%
“…In particular, clinical outcome and follow-up data are often not accessible due to heterogeneity stemming from the many institutions involved. On the other side, it is advertised that integrating all data and analyzing these data using methods from data science, one might be able to improve health care in terms of precision medicine, predictive modeling, clinical decision support and also comparative effectiveness research [26,43,50,61]. This advancement is not impeded by data science, but rather by compliance issues.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we discovered novel radiomic signature that improved clinical prognostic models, results some of which were also validated in independent data. We thereby demonstrated that radiomics has to be regarded 196 as a data science, following stringent statistical study designs, in order to fulfill its role as a clinical decision support system [66,67].…”
Section: Machine Learning To Improve Prognostic Value Of Radiomic Appmentioning
confidence: 99%
“…To integrate radiomic applications in future clinical cancer management, robust and secure infrastructure has to be developed, allowing storage of massive amounts of sensitive patient data, model development and validation, as well as transparent data and method sharing to foster collaborative research [98]. To facilitate collaborative research, novel concepts such as distributed and continuous learning could be valuable tools [66,99,100]. In particular, innovative and open source software, such as PyRadiomics for radiomic feature extraction (https://pyradiomics.readthedocs.io), the 3D Slicer suite for managing image data [101], and BraTumIA for automatic segmentation [102], can contribute in reproducing independent results in the growing radiomic research community.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation